Management of Bacterial Wilt of Tomato (Solanum lycopersicum L.) using Some Plant Resistance Activators - Adedibu, O. B,; Popoola, A. R,; Afolabi, C.G,; Bodunde, J. G.,; Ganiyu, S.A.,; Kazeem, S.A, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Bacterial wilt (Ralstonia solanacearum) is a soil borne plant pathogen, which negatively affects tomato production globally. Plant resistance activators (PRAs): Acibenzolar-S-methyl (ASM), β-Aminobutyric acid (BABA), Salicylic acid (SA) and Acetylsalicylic acid (ASA) were investigated to determine their effectiveness in managing bacterial wilt under screenhouse conditions. PRAs at 25 µg/ml, 50 µg/ml and 75 µg/ml concentrations each, were applied as foliar spray and root drenching to tomato cultivars: Perfect Pee and Roma Round laid out in a Complete Randomized Design with three replications. Seedlings were artificially inoculated with R. solanacearum suspension (6 × 107cfu/ml) using the foliar method. All the PRAs reduced bacterial wilt incidence and severity to the barest minimum. The highest number of fruits, irrespective of the varieties and application method was significantly different (p≤0.05) from the control. However, the least and highest significantly different (p≤0.05) fruit yield (4.60 and 38.70 g/plant) was recorded for foliar spray-treated SA Roma Round and ASA Perfect Pee respectively at 50 µg/ml. In all, ASA foliar spray at 50µg/ml produced significantly higher tomato yield than the other plant activators and untreated controls. This suggests that the use of ASA in controlling bacterial wilt would be effective in integrated disease management program.